IMPACTO DE MEDIDAS DE CONSERVAÇÃO DE ENERGIA APLICADAS EM UM EDIFÍCIO PÚBLICO DE ENSINO SUPERIOR - Babugia, Felipe Pereira; Picchi, Jéssica Castoldi; Giglio, Thalita Gorban Ferreira (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The high-energy consumption of public buildings has mobilized the government to require, through normative instructions, the incorporation of efficiency energy criteria. This paper analyzes the impact of energy efficiency strategies at energy consumption, demand, and annual costs at a public higher education building. Based on energy audit, it was possible to understand the energy consumption by end-use. After that, whole-building energy simulations were performed with Energy Plus software. Through 36 energy efficiency strategies simulated, a possible set of strategies was chosen, considering its application in an existing building. These solutions resulted in a reduction of 58.2% in the annual electricity consumption. The annual demand was reduced by 50.9%, resulting in R$ 34,428.00 of annual energy cost savings. Some action was concentrated in lighting system, responsible for 75% of the building energy consumption. Measures related to the envelope were adopted in order to reduce the high demand of the air conditioning system and to improve user thermal comfort. The incorporation of radiant barrier and high solar reflectance (SR) paints presented little impact on energy consumption (kWh), but significantly impact on energy demand (kW), thus demonstrate the importance of this parameter in building energy efficiency researches.